2020
DOI: 10.3390/nano10102002
|View full text |Cite
|
Sign up to set email alerts
|

Rational Regulation of Surface Free Radicals on TiO2 Nanotube Arrays via Ag2O–AgBiO3 towards Enhanced Selective Photoelectrochemical Detection

Abstract: Due to integrated advances in photoelectrochemical (PEC) functionalities for environment detection applications, one-dimensional (1D) TiO2 nanostructures provide a new strategy (PEC sensors) towards organics detection in wastewater. However, the unidealized selectivity to the oxidation of water and organics limits the PEC detection performance. Herein, we designed a ternary photoanode consisting of Ag2O–AgBiO3/TiO2 nanotube arrays (NTAs) to solve this issue by using a facile one-step precipitation reaction. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…The TEM results suggested that after the addition of ClO − , the surface of the nanoparticles was wrapped by a membrane (whose chemical composition mainly includes Cl, O, and Cr elements), causing agglomeration of the nanoparticles (Figure 4B). And high-resolution TEM analysis showed that the lattice fringe spacings of Ag-Cr NPs and ClO − mixtures were 0.171, 0.243, 0.251 (Figure 4Bb), and 0.278 nm (Figure S4, Supporting Information), corresponding to the (220) plane of Ag 2 O, [63,73] the (111) plane of Ag, [74] the (110) plane of Cr 2 O 3 , [75] and (200) plane of AgCl, [76] respectively. Compared to the crystal planes of Ag-Cr NPs, this result showed that ClO − clearly leaded to the oxidation of Ag-Cr NPs.…”
Section: Quantitative Detection Of Clo − By Ag-cr Nps and Characteriz...mentioning
confidence: 99%
“…The TEM results suggested that after the addition of ClO − , the surface of the nanoparticles was wrapped by a membrane (whose chemical composition mainly includes Cl, O, and Cr elements), causing agglomeration of the nanoparticles (Figure 4B). And high-resolution TEM analysis showed that the lattice fringe spacings of Ag-Cr NPs and ClO − mixtures were 0.171, 0.243, 0.251 (Figure 4Bb), and 0.278 nm (Figure S4, Supporting Information), corresponding to the (220) plane of Ag 2 O, [63,73] the (111) plane of Ag, [74] the (110) plane of Cr 2 O 3 , [75] and (200) plane of AgCl, [76] respectively. Compared to the crystal planes of Ag-Cr NPs, this result showed that ClO − clearly leaded to the oxidation of Ag-Cr NPs.…”
Section: Quantitative Detection Of Clo − By Ag-cr Nps and Characteriz...mentioning
confidence: 99%